2016
DOI: 10.1007/s00432-015-2107-y
|View full text |Cite
|
Sign up to set email alerts
|

Prostate tumor overexpressed 1 expression in invasive urothelial carcinoma

Abstract: Subcellular distribution seems to be the most important feature of PTOV1 expression in UC. Nuclear localization of PTOV1 along with cytoplasmic decrease in PTOV1 expression was identified as putative surrogate for PTOV1-associated cellular proliferation and dedifferentiation in UC. The functional relevance as well as the potential role of PTOV1 as a biomarker in UC remains to be specified in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…PTOV1 was firstly identified and reported to be overexpressed in prostate cancer [14]. Later, it was found that high levels of PTOV1 correlated with poor prognosis of prostate cancer [35], breast cancer [20], urothelial carcinoma [36] and so on. Using tissue microarrays, Sara et al unveiled high expression of PTOV1 in lung cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…PTOV1 was firstly identified and reported to be overexpressed in prostate cancer [14]. Later, it was found that high levels of PTOV1 correlated with poor prognosis of prostate cancer [35], breast cancer [20], urothelial carcinoma [36] and so on. Using tissue microarrays, Sara et al unveiled high expression of PTOV1 in lung cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…In aggressive prostate tumors, PTOV1 stained intensely in the nucleus of local and distal (bones) metastatic cells [33]. In urothelial carcinoma (UC) nuclear staining was significantly more frequent compared to benign tissue and a reduced cytoplasmic expression significantly correlated with higher pathological stage and grade, suggesting a functional shift for PTOV1 from the cytoplasm to the nucleus in the progression of these tumors [42]. These observations are in line with previous reports showing that intense nuclear PTOV1 expression was able to distinguish in a significant manner high-grade urothelial carcinoma [40].…”
Section: Ptov1 Expression In Normal and Cancer Tissuesmentioning
confidence: 99%
“…9 It also has been reported to regulate many types of tumors and is a poor prognosis factor for squamous cell carcinoma, invasive urothelial carcinoma, nasopharyngeal carcinoma, bladder carcinoma, early-stage human laryngeal squamous cell carcinoma, and breast cancer. [10][11][12][13][14][15] A previous study suggested that PTOV1 is a poor prognosis factor for epithelial ovarian cancer; 16 however, the role of PTOV1 in ovarian cancer progression has not been studied. The present study aimed to investigate the role of PTOV1 in ovarian cancer chemotherapy resistance.…”
Section: Introductionmentioning
confidence: 99%